ANALISIS KEMAMPUAN NUMERASI PESERTA DIDIK KELAS IV SD TLOGO TERHADAP PEMECAHAN MASALAH MATEMATIKA - Fataniya Maulida; Heru Purnomo; Ningrum Perwitasari (STKIP Subang, 2024)
The main objective of this study is to explain in detail the numeracy ability of students in answering questions for grade 4 at SD Negeri Tlogo Bantul. This research method uses a qualitative approach with descriptive analysis. This study involved 20 grade4 students of SD Negeri Tlogo. The analytical approach used is to provide AKM (Minimum Competency Assessment) questions and interview guides to research participants. The research approach that utilizes student work results uses reference variables obtained from interview results. Furthermore, the research topic is determined with an explanation that tries to describe the talents of the research subjects. The results of the study indicate that grade 4 students of SD Negeri Tlogo, Bantul have numeracy abilities for solving students' mathematical problems in the high category, namely 5 students or 25%, then 6 students or 30% are in the medium category, and 9 students or 45% are in the low category. Students in the medium category are encouraged to continue learning and practicing their numeracy skills so that they are more comfortable with the challenges of solving mathematical problems. Students in the low group are required to receive assistance from educators in order to continue learning and practicing solving mathematical problems.